Analisis Variasi Gaya Belajar Peserta Didik Sekolah Dasar dalam Memaksimalkan Pembelajaran - Sholikhah; Ida Dwijayanti; Sumarno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract, The background that drives this research is that students still experience difficulties in understanding their learning styles, each student has a different learning style, in fact each student learns with a different style for each lesson. The focus of the problem in this research is the learning style used by class VI students at SD Negeri 3 Wonokerto. The aim of this research is to determine the learning styles used by fifth grade students at SD Negeri 3 Wonokerto. The method used in this research is a descriptive qualitative approach. This research was obtained through data sources including class VI teachers and 8 class VI students as samples for this research. Data collection procedures were obtained through observation, interviews, documentation and questionnaires. The research results show that class VI students at SD Negeri 3 Wonokerto do not only use one learning style, they also use a combination of two other learning styles. This shows that the eight students use or have varied learning styles with a tendency for different learning style modalities between the three learning style modalities, visual, auditory and kinesthetic.